Tibial Osteosynthesis Associated with Medial Patellar Luxation Correction in a Bitch - Fogolin, Isabela; Ribeiro de Andrade, Caroline; Galhardo Franco, Guilherme (Acta Scientiae Veterinariae, 2024)
Background: Locking bone plates are fixation systems that neutralize the compressive loads applied to fractures. They require minimal contact with the bone tissue, and are commonly used for the repair of tibial diaphyseal fractures. Patellar luxation is one of the most common orthopedic conditions in small animals. There are a number of surgical techniques described for correction of this pathology aiming to realign the extensor mechanism of the stifle joint and reestablish the function of the stifle joint. The aim of this study was to report the use of a combination of an osteosynthesis technique with a locking plate for tibial facture repair with tibial tuberosity transposition and imbrication of the lateral retinaculum for correction of patellar luxation. Case: A 5-year-old bitch was presented with left pelvic limb lameness following a traumatic entrapment of the limb. Orthopedic and radiographic examinations showed a comminuted diaphyseal fracture in the left tibia and fibula, and left-sided medial patella dislocation in relation to the trochlear groove. The fracture was repaired by placement of a locking plate on the medial aspect of the tibia. The surgical incision was then extended cranially to allow correction of the patellar luxation by transposition of the tibial tuberosity: an oscillating saw was used to perform an osteotomy of the tibial tuberosity; the tibial crest was laterally translocated and transfixed with Kirschner pins. Medial retinaculum release and imbrication of the lateral retinaculum was also performed. Discussion: There are a wide range of bone fixation methods for correction of comminuted tibial diaphyseal fractures. Selection of the appropriate method should take into account biological factors (age and general condition of the animal, involvement of adjacent soft tissues, and degree of blood supply), mechanical factors (classification and degree of stability of the fracture, size and activity level of the patient, and number of limbs involved), and practical factors (financial limitations and surgeon’s preference). In this case a locking plate was selected, a fixation system where stability is provided by the attachment of the screw head to the plate. In this case, at 30 days postoperatively the radiographs showed insufficient bone callus formation. However, bone healing time in adult animals varies from 16 to 30 weeks, so delayed union cannot be diagnosed so early. The occurrence of patellar luxation after the traumatic episode in an adult animal, suggests that it is a traumatic condition. However, animals with patellar luxation may remain asymptomatic until a traumatic soft tissue injury occurs, so classifying this case as strictly traumatic is controversial. Surgical correction of patellar luxation aims to establish alignment of the extensor mechanism of the stifle joint and stabilization of the patella in the femoral trochlea. In order to achieve this objective, a combination of surgical techniques is used, including tibial tuberosity transposition, corrective osteotomies and trochleoplasties, and release or reconstruction of the soft tissues adjacent to the patella. In this case the combination of osteosynthesis techniques with locked plate, tibial tuberosity transposition and lateral retinaculum imbrication for the correction of patellar dislocation was effective in correcting a pre-existing pathology as well as the acute tibial fracture. Keywords: orthopedics, fracture, dislocation, patelar, stifle, canine. Título: Osteossíntese de tíbia associada à correção de luxação medial de patela em uma cadela Descritores: ortopedia, fratura, deslocamento, patelar, joelho, canino.